Effect of the Brand Image, Product Quality, And Price on The Consumer Decisions At PT. Duta Agung Anugerah Medan - Vincent Vincent; Rahmat Alamsyah Harahap; Tommy Wijaya (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
Methods of data collection with interviews, questionnaires, and documentation. The data analysis method used is multiple linear regression. The number of samples in this study using a saturated sampling technique was 40 consumers and 30 respondents from PT. Duta Agung Anugerah Medan. The conclusion is that the effect of brand image, product quality, and price simultaneously (f test) has a positive effect on consumer decisions. F count 92.051 > F table 2.86 with sig. from 0.000 < 0.05. Partially (t-test) the brand image of t count 4.805 > t table 2.026 and a sig. of 0.000 <0.05 then the quality of the product t count 3.890 > t table 2.026 and a sig. of 0.000 < 0.05, the value of t count 0.219 < t table 2.026 and a sig. from 0.828 > 0.05. The results of the Adjusted R Square coefficient of determination are 0.875, meaning that brand image, product quality, and price affect consumer decisions with a level of 87.5%, while the remaining 12.5% can be explained by other factors or external variables. Research Model..